Necrotizing Granulomas within the Periprosthetic Tissues of Cemented and Cementless Total Arthroplasties - Boss, J. H.; Shajrawi, I.; Luria, M.; Mendes, D. G. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
Necrotizing granulomas were found in the pseudocapsule or interfacial membrane of two patients with an aseptically loosened cemented total hip arthroplasty and in one patient with an aseptically loosened cementless knee arthroplasty. The environs of the necrotizing granulomas disclosed prosthetic debris-induced foreign body granulomatous, chronic inflammatory and cicatrizing changes. Particulate breakdown products of polyethylene and finely dispersed metallic particles were present in the necrotic core, stroma and macrophages of the necrotizing granulomas. A review of the literature and the authors’ personal experience attests to the rarity of such granulomas in the periprosthetic tissues. Polyethylene being non-antigenic, it is suggested that an allergic-pathergic reaction to metallic ions released in loco from the prosthesis itself, from the deposited metallic wear particles or from both accounts for the development of the necrotizing granulomas.
Keywords: Necrotizing granuloma; allergic and pathergic reaction; arthroplasty; biomaterials; metallosis